Effects of organic acids dietary supplementation in soybean meal-based diets on growth performance and nutrient utilization in hybrid grouper (Epinephelus fuscoguttatus x E. lanceolatus) juveniles - Abang Zamhari, Dayang Nur Jazlyn; Shapawi, Rossita; Lim, Leong Seng; Mohd Faudzi, Norfazreena; Lin, Yu Hung; Zhuo, Li Chao; Yong, Christina Seok Yien; Lau, Benjamin Yii Chung; Yong, Annita Seok Kian (Elsevier B.V., 2025)
A 10-week feeding experiment was carried out to study the effects of supplementing citric and butyric acids in soybean meal (SBM) based diets for hybrid grouper (Epinephelus fuscoguttatus x E. lanceolatus) juveniles. Seven experimental diets were formulated to replace fishmeal (FM) with SBM at the levels of 30 % (SBM30) and 40 % (SBM40) as a base to substitute FM, SBM30 with the supplementation of 3 % citric acid and 1 % butyric acid (SBM30 +CA+BA), SBM40 with the supplementation of 3 % citric acid (SBM40 +CA), SBM40 with the supplementation of 1 % butyric acid (SBM40 +BA), SBM40 with the supplementation of 3 % citric acid and 1 % butyric acid (SBM40 +CA+BA) and with FM diet being the control. Triplicate groups of 16 fish (11.50 ± 0.6 g) in 21 tanks were fed respective experimental diets. Results showed that the highest weight gain, specific growth rate and protein efficiency ratio was recorded in fish fed SBM30 +CA+BA but it was not significantly different from fish fed control FM diet (p > 0.05) while fish fed SBM40 showed the lowest performance (p > 0.05). However, comparing the SBM40 treatments, fish fed SBM40 +CA showed the highest (p > 0.05). No significant differences were observed among the treatments for hepatosomatic index. Meanwhile, for the viscera-somatic index, fish fed SBM40 +BA was significantly lowest while FM, SBM30 and SBM30 +CA+BA showed no significant differences. Between the SBM40 treatments, SBM40 +CA showed the highest but no significant differences with SBM40 and SBM40 +CA+BA. Fish fed SBM40 +CA+BA also showed increased crude protein for whole body composition and apparent digestibility coefficient of protein. Based on the results, 30 % replacement of SBM with the combination of citric and butyric acid showed better growth while for 40 % replacement of SBM, supplementation of citric acid proved to give better results compared to butyric acid and without the supplementation of organic acid.